Negative plate, battery and electric equipment
By adding 0.1%-5% silica nanowires to the negative electrode active layer of the negative electrode sheet, the side reaction problems caused by the increase of conductive agent are solved, the flexibility and liquid retention capacity of the negative electrode sheet are improved, and the first effect of the battery is extended and cycle life.
Patent Information
- Application Number
- CN202411550362.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-07
AI Technical Summary
When the existing negative electrode sheets increase the conductive agent, side reactions are easily caused, resulting in a decrease in battery capacity and a decrease in cycle life, affecting the battery's service life and performance stability.
Add 0.1%-5% silica nanowires to the negative electrode active layer of the negative electrode sheet. Through its high specific surface area and mechanical strength, the electrolyte infiltration effect and flexibility of the negative electrode sheet are improved, and the embeddedness and removal of active ions are promoted.
It improves the flexibility and liquid retention ability of the negative electrode sheet, extends the first effect and cycle life of the battery, and ensures the service life and performance stability of the battery.
Smart Images

Figure CN119400801A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the field of battery technology. Specifically, the present application relates to a negative electrode sheet, a battery and an electrical device. Background Art
[0002] In the field of batteries, the performance of the negative electrode sheet has a significant impact on the overall performance of the battery. In order to improve the liquid retention capacity of the negative electrode sheet, this can be achieved by increasing the content of conductive carbon black in the negative electrode sheet, which can effectively further promote the diffusion and transfer of active ions during the charge and discharge process.
[0003] However, as the amount of conductive agent added increases, complex side reactions are likely to occur at the interface between the conductive agent and the electrolyte, which will cause the battery capacity to decay and the cycle life to drop significantly, restricting the battery's service life and performance stability. Summary of the invention
[0004] One purpose of the embodiments of the present application is to provide a new technical solution for a negative electrode sheet, a battery and an electrical device.
[0005] According to a first aspect of an embodiment of the present application, a negative electrode sheet is provided, comprising:
[0006] Anode current collector;
[0007] The negative electrode active layer comprises silicon dioxide nanowires, and the mass proportion of the silicon dioxide nanowires in the negative electrode active layer is 0.1%-5%.
[0008] Optionally, the mass proportion of the silicon dioxide nanowires in the negative electrode active layer is 0.5%-2.0%.
[0009] Optionally, the negative electrode active layer includes a negative electrode active material and a plurality of silicon dioxide nanowires, the plurality of silicon dioxide nanowires are overlapped to form a three-dimensional framework, and at least a portion of the negative electrode active material is filled in the three-dimensional framework.
[0010] Optionally, the negative electrode active material accounts for 80%-98% by mass of the negative electrode active layer.
[0011] Optionally, the dielectric constant of the silicon dioxide nanowires is in the range of 1.5-4.0.
[0012] Optionally, the negative electrode active layer comprises a first dressing layer and a second dressing layer, the first dressing layer is arranged on at least one side of the surface of the negative electrode current collector, and the second dressing layer is arranged on a side of the first dressing layer away from the negative electrode current collector;
[0013] The first dressing layer and / or the second dressing layer include silicon dioxide nanowires.
[0014] Optionally, the silicon dioxide nanowire has a pore structure, and the pore size of the pore structure ranges from 2nm to 50nm.
[0015] Optionally, the length of the silicon dioxide nanowire is in the range of 0.5 μm-50 μm; and / or, the diameter of the silicon dioxide nanowire is in the range of 5 nm-100 nm; and / or, the specific surface area of the silicon dioxide nanowire is in the range of 50 m 2 / g-1000m 2 / g.
[0016] Optionally, the single-surface density of the negative electrode active layer is in the range of 500 g / m 2 -700g / m 2 .
[0017] Optionally, the negative electrode active layer also includes a conductive agent, a thickener and a binder; the conductive agent accounts for 0-5% by mass of the negative electrode active layer, the thickener accounts for 0.5%-5% by mass of the negative electrode active layer, and the binder accounts for 0.5%-5% by mass of the negative electrode active layer.
[0018] According to a second aspect of an embodiment of the present application, a battery is provided, comprising the negative electrode sheet described in the first aspect.
[0019] According to a third aspect of an embodiment of the present application, an electrical device is provided, and the electrical device includes the battery described in the third aspect.
[0020] A technical effect of this application is:
[0021] The embodiment of the present application provides a negative electrode sheet, which includes a negative electrode current collector; a negative electrode active layer, the negative electrode active layer is arranged on at least one side surface of the negative electrode current collector; the negative electrode active layer includes silicon dioxide nanowires, and the mass proportion of the silicon dioxide nanowires in the negative electrode active layer is 0.1%-5%. On the one hand, the silicon dioxide nanowires can enhance the electrolyte infiltration effect of the negative electrode sheet, ensuring the flexibility and liquid retention capacity of the negative electrode sheet; on the other hand, it helps the active ions in the electrolyte to be more easily embedded and removed, thereby ensuring the first effect and cycle life of the battery.
[0022] Other features and advantages of the present application will become apparent from the following detailed description of exemplary embodiments of the present application with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] The accompanying drawings, which are incorporated in and constitute a part of the specification, illustrate embodiments of the application and, together with the description, serve to explain the principles of the application.
[0024] Figure 1A schematic diagram of a negative electrode sheet provided in accordance with an embodiment of the present application. DETAILED DESCRIPTION
[0025] Various exemplary embodiments of the present application will now be described in detail with reference to the accompanying drawings. It should be noted that unless otherwise specifically stated, the relative arrangement of components and steps, numerical expressions and numerical values set forth in these embodiments do not limit the scope of the present application.
[0026] The embodiments of the present application will be described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and should not be understood as limiting the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.
[0027] In batteries, improving the flexibility and liquid retention capacity of the battery's negative electrode sheet can increase the rate of active ion transport and the battery's rate performance, while alleviating the damage to the electrode structure caused by the volume expansion effect of the negative electrode active material. However, it is difficult to balance the improvement of the flexibility and liquid retention capacity of the negative electrode sheet with the improvement of the first effect and cycle life.
[0028] The embodiment of the present application adds silicon dioxide nanowires to the negative electrode active layer of the negative electrode sheet, thereby improving the flexibility and liquid retention capacity of the negative electrode sheet and ensuring the charge and discharge efficiency and cycle life of the battery including the negative electrode sheet.
[0029] Reference Figure 1 , the embodiment of the present application provides a negative electrode sheet, the negative electrode sheet comprising:
[0030] Negative electrode current collector 1;
[0031] A negative electrode active layer 2, wherein the negative electrode active layer 2 is disposed on at least one side surface of the negative electrode current collector 1;
[0032] The negative electrode active layer 2 comprises:
[0033] The silicon dioxide nanowires account for 0.1% to 5% of the mass of the negative electrode active layer.
[0034] In this embodiment, the negative electrode active layer 2 may be coated on one side of the negative electrode current collector 1 , or may be coated on both sides of the negative electrode current collector 1 .
[0035] In this embodiment, silica nanowires refer to nanoscale linear silica materials with at least one dimension at the nanometer level in three dimensions. During the preparation of the negative electrode active layer 2 of the negative electrode sheet, silica nanowires can be added to the negative electrode active layer 2 to replace part of the conductive agent. At the same time, silica nanowires have high strength and toughness. Silica nanowires can support the entire negative electrode active layer 2 like a "skeleton", thereby improving the flexibility and mechanical strength of the negative electrode sheet, and obtaining a negative electrode sheet with high flexibility and liquid retention capacity.
[0036] At the same time, silicon dioxide nanowires have a large specific surface area, thereby increasing the total specific surface area of the negative electrode active layer 2 in the negative electrode sheet. A large specific surface area means that the contact area between the electrode material and the electrolyte is increased, which helps the active ions in the electrolyte to be more easily embedded and released, thereby improving the initial efficiency and cycle life of the battery, and ensuring the battery's service life and performance stability.
[0037] Moreover, silica nanowire materials are non-toxic and non-flammable, which helps to improve the safety performance of batteries.
[0038] In one embodiment, the negative electrode current collector 1 can be copper foil or carbon-coated copper foil to effectively collect electrons generated by the electrode reaction, improve the transfer efficiency of electrons inside the battery, and thus increase the output power and stability of the battery.
[0039] In the embodiment of the present application, when the content of silica nanowires in the negative electrode active layer 2 is relatively small, for example, when the mass proportion of silica nanowires in the negative electrode active layer 2 is less than 0.1%, the wetting effect of the silica nanowires in the negative electrode active layer of the electrode sheet is limited, and the contribution to the specific surface area of the negative electrode active layer is not large, thereby limiting the liquid retention capacity and charge and discharge capacity of the negative electrode sheet; and when the content of silica nanowires in the negative electrode active layer 2 is relatively large, for example, when the mass proportion of silica nanowires in the negative electrode active layer 2 is greater than 5.0%, excessive addition of silica nanowires limits the content of the negative electrode active material, resulting in a lower charge and discharge capacity of the negative electrode sheet.
[0040] The negative electrode sheet provided in the embodiment of the present application includes a negative electrode current collector 1; a negative electrode active layer 2, wherein the negative electrode active layer 2 is disposed on at least one side surface of the negative electrode current collector 1; the negative electrode active layer 2 includes silicon dioxide nanowires, and the mass proportion of silicon dioxide nanowires in the negative electrode active layer is 0.1%-5%. Adding silicon dioxide nanowires to the negative electrode sheet and setting the mass proportion of silicon dioxide nanowires to be in the range of 0.1%-5% can, on the one hand, enhance the electrolyte infiltration effect of the negative electrode sheet and ensure the flexibility and liquid retention capacity of the negative electrode sheet; on the other hand, it helps to embed and remove active ions in the electrolyte more easily, thereby ensuring the first effect and cycle life of the battery.
[0041] In one embodiment, the mass proportion of the silicon dioxide nanowires in the negative electrode active layer is 0.5%-2.0%.
[0042] The negative electrode sheet provided in the embodiment of the present application controls the mass proportion of silicon dioxide nanowires in the negative electrode active layer 2 within the range of 0.5%-2.0%, for example, the percentage content of silicon dioxide nanowires in the negative electrode active layer 2 is 0.8%, 1.0%, 1.3% or 1.8%, which further improves the flexibility and liquid retention capacity of the negative electrode sheet, and can improve the initial efficiency and cycle life of the battery's charge and discharge.
[0043] In one embodiment, the negative electrode active layer includes a negative electrode active material and a plurality of silicon dioxide nanowires. The plurality of silicon dioxide nanowires are overlapped to form a three-dimensional framework, and at least a portion of the negative electrode active material is filled in the three-dimensional framework.
[0044] Specifically, the silica nanowires also have good electrolyte affinity and wettability. The overlap between adjacent silica nanowires can generate new holes in the negative electrode active layer 2, which can enhance the electrolyte infiltration effect of the negative electrode sheet, improve the interface compatibility and ionic conductivity of the negative electrode sheet, and ensure the liquid retention capacity of the negative electrode sheet.
[0045] In this embodiment, the three-dimensional framework formed by the overlap of multiple silicon dioxide nanowires provides a strong supporting structure, and the negative electrode active material is filled inside the three-dimensional framework, which further enhances the hardness and strength of the negative electrode material, improves the mechanical properties of the battery, and enables the entire negative electrode material to maintain good stability when subjected to external forces. In addition, the silicon dioxide nanowires can better bridge the main component material, increase the flexibility of the negative electrode sheet, reduce the risk of cracking and falling of the negative electrode sheet, and improve the yield rate of the negative electrode sheet.
[0046] In addition, silica nanowires have good mechanical strength, and the three-dimensional framework constructed by silica nanowires helps to optimize the active ion transport behavior during the charging process and improve the polarization of the negative electrode and the battery.
[0047] In one embodiment, when the mass proportion of the negative electrode active material in the negative electrode active layer is 80%-98%, that is, more active substances in the negative electrode active material can participate in the charge and discharge process of the battery, thereby improving the energy density of the battery.
[0048] In one embodiment, the negative electrode active material may include a combination of one or more of graphite materials, silicon-based materials, tin-based materials, and lithium titanate materials to ensure the charge and discharge capacity of the negative electrode sheet while ensuring the stability of the negative electrode sheet.
[0049] Among them, the graphite material can be a combination of one or more of artificial graphite, natural graphite, soft carbon, hard carbon, mesophase carbon microspheres and carbon fibers; the silicon-based material can be a combination of one or more of elemental silicon, silicon oxide, silicon alloy and composite silicon; the tin-based material can be a combination of one or both of tin oxide and tin alloy.
[0050] In one embodiment, the dielectric constant of the silicon dioxide nanowires is in the range of 1.5-4.0.
[0051] In this embodiment, the silica nanowires have a relatively low dielectric constant (ε) of 1.5-4.0. When the silica nanowires replace part or all of the conductive agent and are added to the negative electrode active layer 2 of the negative electrode sheet, excessive consumption of electrolyte caused by the growth of SEI film on the surface of the negative electrode active layer 2 material can be avoided, thereby improving the initial efficiency and cycle stability of the battery.
[0052] The test method of the dielectric constant includes: preparing the silicon dioxide nanowires into a sample with a size of about 10mm×10mm×1mm, and placing the sample in a vacuum drying oven for drying; coating the upper and lower surfaces of the sample with indium gallium electrodes to form a capacitor structure; connecting the sample coated with electrodes to an impedance analyzer; setting the test frequency range of the impedance analyzer; starting the impedance analyzer for testing, and recording and saving the test results.
[0053] In one embodiment, the negative electrode active layer 2 includes a first dressing layer and a second dressing layer, wherein the first dressing layer is disposed on at least one side of the negative electrode current collector 1, and the second dressing layer is disposed on a side of the first dressing layer away from the negative electrode current collector 1;
[0054] The first dressing layer and / or the second dressing layer include silicon dioxide nanowires.
[0055] In this embodiment, the negative electrode active layer 2 can be formed on the negative electrode current collector 1 by a double-layer coating process to form a first dressing layer and a second dressing layer on the surface of the negative electrode current collector 1, and one of the first dressing layer and the second dressing layer can be added with silica nanowires, or both the first dressing layer and the second dressing layer can be added with silica nanowires; by adjusting the position of the silica nanowires in the negative electrode active layer of the negative electrode sheet, the performance of ion and electron transmission in the battery can be improved.
[0056] When silica nanowires are added to both the first dressing layer and the second dressing layer, the contents of the silica nanowires in the first dressing layer and the second dressing layer are different, for example, the content of the silica nanowires in the second dressing layer is greater than that in the first dressing layer, so as to enhance the electrolyte infiltration effect of the negative electrode sheet and the liquid retention capacity of the negative electrode sheet.
[0057] In addition, the negative electrode active layer 2 can be formed on the negative electrode current collector 1 by a multi-layer coating process to obtain three, four or even more layers of coating layers on the negative electrode current collector 1, and silicon dioxide nanowires are added to one or more of the layers.
[0058] In one embodiment, among the multiple layers of dressing layers coated on the negative electrode current collector 1 , silicon dioxide nanowires are added to a layer close to the negative electrode current collector 1 , which can enhance the transmission efficiency of ions and electrons between the negative electrode active layer and the negative electrode current collector.
[0059] In one embodiment, the silicon dioxide nanowire has a pore structure, and the pore size of the pore structure ranges from 2 nm to 50 nm.
[0060] In this embodiment, the silica nanowires can be modified by in-situ growth or etching to obtain mesoporous silica nanowires. The mesopores in the silica nanowires form a pore structure in the silica nanowires, thereby improving the liquid retention capacity of the negative electrode sheet.
[0061] In one embodiment, the pore structure has a pore size range of 5nm-30nm. By generating multiple mesoporous pore structures in the silica nanowires, the specific surface area of the silica nanowires can be further increased, which helps to embed and remove ions in the electrolyte, thereby improving the initial efficiency and cycle life of the battery, and ensuring the service life and performance stability of the battery.
[0062] In one embodiment, the length of the silicon dioxide nanowire is in the range of 0.5 μm-50 μm, such as the length of the silicon dioxide nanowire is 1.0 μm, 5.0 μm, 20 μm or 40 μm; and / or, the diameter of the silicon dioxide nanowire is in the range of 5 nm-100 nm, such as the diameter of the silicon dioxide nanowire is 10 nm, 30 nm, 50 nm or 80 nm; and / or, the specific surface area of the silicon dioxide nanowire is in the range of 50 m 2 / g-1000m 2 / g, for example, the specific surface area of silica nanowires is 80m 2 / g, 200m 2 / g、500m 2 / g or 800m 2 / g.
[0063] In this embodiment, silicon dioxide nanowires with a high aspect ratio are added to the negative active layer 2 of the negative electrode sheet, for example, silicon dioxide nanowires with a length in the range of 0.5 μm-50 μm and a diameter in the range of 5 nm-100 nm are added. The increase in the aspect ratio of the nanowires means that the structure of the three-dimensional framework formed by the silicon dioxide nanowires is more stable, which is beneficial to improving the structural stability of the negative electrode sheet.
[0064] In one embodiment, the single surface density of the negative electrode active layer 2 is in the range of 500 g / m 2 -700g / m 2 .
[0065] In this embodiment, 500 g / m 2 -700g / m 2 The single-surface density can form a thick electrode system negative electrode sheet, for example, the single-surface density of the negative electrode active layer 2 is 550g / m 2 , 600g / m 2 , 620g / m 2 or 680g / m 2 , that is, to achieve a thicker negative electrode active layer 2 on the negative electrode current collector 1 of the negative electrode sheet, which helps to improve the energy density of the battery, so that the battery can store more energy under the same volume or weight; and improve the structural stability of the electrode sheet, reduce the volume change during the charge and discharge cycle, thereby improving the cycle life and stability of the battery.
[0066] In one embodiment, the negative electrode active layer 2 includes a negative electrode active material, a conductive agent, silicon dioxide nanowires, a thickener and a binder;
[0067] The mass proportion of the negative electrode active material in the negative electrode active layer is 80%-98%, the mass proportion of the conductive agent in the negative electrode active layer is 0-5%, the mass proportion of the silicon dioxide nanowire in the negative electrode active layer is 0.1%-5%, the mass proportion of the thickener in the negative electrode active layer is 0.5%-5%, and the mass proportion of the binder in the negative electrode active layer is 0.5%-5%.
[0068] In this embodiment, during the preparation process of the negative electrode active layer 2 of the negative electrode sheet, since the conductivity requirement of the negative electrode active layer on the negative electrode sheet is relatively low, by adding silicon dioxide nanowires to the negative electrode active layer 2, at least part of the conductive agent can be replaced to ensure the active capacity of the negative electrode sheet.
[0069] In one embodiment, the conductive agent may include a combination of one or more of conductive carbon black, carbon nanotubes, graphene, conductive graphite, and carbon fiber materials.
[0070] Among them, the conductive carbon black material can be one or a combination of acetylene black, furnace black, channel black, thermal black, lamp black and Ketjen black; the carbon nanotube can be a combination of one or more carbon nanotubes with different tube diameters (the tube diameter range can be 1nm-100nm) and different tube lengths (the tube length can be 50nm-100μm); the graphene can be a combination of one or more graphene with different numbers of layers (the number of graphene layers can range from 1 to 1000 layers); the conductive graphite can be one or a combination of two of artificial graphite and natural graphite.
[0071] The thickener and binder may be conventional thickeners and binders in the art, without any specific limitation.
[0072] An embodiment of the present application provides a battery, which includes the above-mentioned negative electrode sheet, thereby ensuring the initial efficiency and cycle life of the battery.
[0073] In one embodiment, the battery comprises a positive electrode sheet, a separator and the negative electrode sheet described above;
[0074] The separator is disposed between the positive electrode sheet and the negative electrode sheet.
[0075] In this embodiment, the separator includes but is not limited to one of polyethylene, polypropylene and polyvinylidene fluoride or a composite of multiple separators to effectively isolate the physical contact between the positive electrode sheet and the negative electrode sheet.
[0076] In the negative electrode sheet of the battery, the negative electrode sheet includes a negative electrode current collector 1; a negative electrode active layer 2, the negative electrode active layer 2 is arranged on at least one side surface of the negative electrode current collector 1; the negative electrode active layer 2 includes silicon dioxide nanowires, and the mass proportion of the silicon dioxide nanowires in the negative electrode active layer is 0.1%-5%. On the one hand, the silicon dioxide nanowires can enhance the electrolyte infiltration effect of the negative electrode sheet, ensuring the flexibility and liquid retention capacity of the negative electrode sheet; on the other hand, it helps the active ions in the electrolyte to be more easily embedded and removed, thereby ensuring the first effect and cycle life of the battery.
[0077] In this embodiment, the battery may be a lithium ion battery or a sodium ion battery.
[0078] When the battery is a lithium ion battery, the positive electrode active material on the positive electrode sheet in the lithium ion battery includes a combination of one or more of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and olivine structured lithium-containing phosphate.
[0079] When the battery is a sodium ion battery, the positive electrode active material on the positive electrode sheet in the sodium ion battery includes a combination of one or more of transition metal oxides, polyanionic compounds, organic polymers and Prussian blue materials to ensure the charge and discharge capacity of the battery.
[0080] An embodiment of the present application provides an electrical device, which includes the above-mentioned battery.
[0081] The technical solution of the present application is further illustrated below by means of specific examples and comparative examples, wherein the batteries obtained in the examples and comparative examples are all laminated batteries, and the designed capacity is all 1.7 Ah.
[0082] Example 1
[0083] Negative plate:
[0084] The negative electrode active material (artificial graphite 96g), silicon dioxide nanowires (1.0g), thickener (CMC2g), and binder (SBR1.0g) were mixed evenly in a deionized water system to obtain a negative electrode slurry, and then the negative electrode slurry was evenly coated on a copper foil to obtain a negative electrode sheet;
[0085] Positive electrode:
[0086] The positive electrode active material lithium iron phosphate (97 g), conductive agent (CNT 1.0 g), and binder (PVDF 2.0 g) were fully stirred and mixed in an N-methylpyrrolidone (NMP) solvent system, and then coated on an aluminum foil to obtain a positive electrode sheet.
[0087] Diaphragm:
[0088] Polypropylene diaphragm is used.
[0089] Electrolyte:
[0090] Ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 1:1:1 to prepare a 1M LiPF 6 of electrolyte.
[0091] The positive electrode sheet, negative electrode sheet and separator are wound to obtain a core, which is packaged with aluminum-plastic film, baked under vacuum for 48 hours to remove moisture, and then injected with electrolyte. After formation and capacity division, a soft-pack battery is made.
[0092] Example 2
[0093] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0094] A conductive agent (0.8 g of SP conductive carbon black) was added to the negative electrode active layer of the negative electrode sheet, and the amount of silica nanowires added was adjusted to 0.2 g.
[0095] Example 3
[0096] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0097] A conductive agent (0.5 g of SP conductive carbon black) was added to the negative electrode active layer of the negative electrode sheet, and the amount of silica nanowires added was adjusted to 0.5 g.
[0098] Example 4
[0099] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0100] A conductive agent (0.2 g of SP conductive carbon black) was added to the negative electrode active layer of the negative electrode sheet, and the amount of silica nanowires added was adjusted to 0.8 g.
[0101] Example 5
[0102] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0103] The amount of silica nanowires added was adjusted to 0.8 g.
[0104] Example 6
[0105] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0106] The amount of silica nanowires added was adjusted to 0.5 g.
[0107] Example 7
[0108] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0109] The amount of silica nanowires added was adjusted to 0.2 g.
[0110] Example 8
[0111] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0112] The amount of silica nanowires added was adjusted to 0.1 g.
[0113] Example 9
[0114] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0115] The amount of silica nanowires added was adjusted to 2.0 g.
[0116] Example 10
[0117] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0118] The amount of silica nanowires added was adjusted to 3.0 g.
[0119] Embodiment 11
[0120] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0121] The amount of silica nanowires added was adjusted to 4.0 g.
[0122] Example 12
[0123] This embodiment prepares a battery, which is different from the embodiment 1 only in that:
[0124] The amount of silica nanowires added was adjusted to 5.0 g.
[0125] Comparative Example 1
[0126] This comparative example prepares a battery, which differs from Example 1 only in that:
[0127] A conductive agent (0.8 g of SP conductive carbon black) was added to the negative electrode active layer of the negative electrode sheet, but no silica nanowires were added.
[0128] Comparative Example 2
[0129] This comparative example prepares a battery, which differs from Example 1 only in that:
[0130] No conductive agent and silicon dioxide nanowires are added to the negative electrode active layer of the negative electrode sheet.
[0131] Comparative Example 3
[0132] This comparative example prepares a battery, which differs from Example 1 only in that:
[0133] Negative electrode active material (96.95 g of artificial graphite) and silicon dioxide nanowires (0.05 g) were added to the negative electrode active layer of the negative electrode sheet.
[0134] Comparative Example 4
[0135] This comparative example prepares a battery, which differs from Example 1 only in that:
[0136] Negative electrode active material (91 g of artificial graphite) and silicon dioxide nanowires (6.0 g) were added to the negative electrode active layer of the negative electrode sheet.
[0137] Performance Testing:
[0138] Pole flexibility test:
[0139] Select shaft rods with different curvature radii (0.3mm, 0.5mm, 0.8mm, 1mm, 1.2mm, 1.5mm, 2mm, 2.5mm, 3mm, 5mm, 7.5mm), each with a length of 80mm, and press the pole piece on the shaft rods with different diameters in turn. The pressing order is arranged from large to small in diameter, and bend it around the rod within (2-3) seconds. After bending, the two thumbs are symmetrical to the center line of the shaft rod. Use visual inspection or a 4x magnifying glass to observe whether the pole piece has reticulation, cracks, powder loss, peeling and other damage phenomena, and record the minimum shaft rod curvature radius when the pole piece is bent on shaft rods of different diameters without pole piece damage; the minimum shaft rod curvature radius represents the flexibility of the pole piece.
[0140] Fluid retention test:
[0141] The negative electrode sheets prepared in the embodiment and the comparative example were baked at 120°C for 12 hours, and the mass of the negative electrode sheets after baking was recorded. Under a 25°C environment, the baked negative electrode sheets were immersed in the electrolyte for 48 hours and then taken out, and the mass of the negative electrode sheets after being immersed in the electrolyte was recorded. The liquid retention capacity of the negative electrode sheets was calculated, and the calculation formula for the liquid retention capacity was:
[0142] Liquid retention capacity = (mass of the negative electrode sheet after being soaked in electrolyte - mass of the negative electrode sheet after baking) / mass of the coating of the negative electrode sheet.
[0143] Resistivity test:
[0144] The negative electrode sheets prepared in the embodiment and the comparative example are laid flat in the test chamber of the resistance meter, and the test probe is allowed to contact the surface of the negative electrode sheet to perform the test, and the resistivity of the negative electrode sheet is read from the instrument computer.
[0145] First charge and discharge test:
[0146] At 25°C, the battery was charged at 0.1C constant current and constant voltage to 100% SOC, aged at 45°C for 24h, and discharged at 0.1C constant current to 0% SOC. The charging capacity and discharging capacity were recorded, and the first charge and discharge efficiency was calculated.
[0147] Full battery first efficiency = discharge capacity / charge capacity*100%
[0148] Cycle life test:
[0149] The battery was charged at 1C at 45°C to a voltage of 3.8V, left for 10 min, and then discharged at a discharge rate of 1C to a voltage of 2.0V. This cycle was repeated 500 times, and the capacity retention rate was recorded.
[0150] Capacity retention rate after 500 cycles (%) = discharge specific capacity after 500 cycles / discharge specific capacity after the third cycle*100%.
[0151] The test results of the batteries in the above embodiments and comparative examples are shown in Table 1 below.
[0152] Table 1
[0153]
[0154]
[0155] It can be seen from the electrodes and batteries of Examples 1 and 5 to 9 that as the amount of silicon dioxide nanowires added increases within the range of 0.2%-2.0%, the flexibility and liquid retention capacity of the electrodes are continuously improved, and the cycle life of the batteries is also increased.
[0156] From the comparison between Example 2 and Comparative Example 1, it can be seen that the addition of silicon dioxide nanowires (and the addition of conductive carbon black at the same time) can increase the flexibility and liquid retention capacity of the electrode and improve the initial efficiency of the battery.
[0157] From the comparison of Examples 1, 5-12 and Comparative Example 2, it can be seen that the addition of silicon dioxide nanowires (without the addition of conductive carbon black) can increase the flexibility and liquid retention capacity of the electrode and improve the cycle life of the battery.
[0158] From the comparison of Examples 1, 5-12 and Comparative Example 3, it can be seen that when the addition amount of silicon dioxide nanowires is less than 0.1%, the flexibility and liquid retention capacity of the electrode as well as the first efficiency and cycle life of the battery are significantly reduced.
[0159] From the comparison of Examples 1, 5-12 and Comparative Example 4, it can be seen that when the addition amount of silicon dioxide nanowires is greater than 5%, the improvement of the flexibility and liquid retention capacity of the electrode is very limited, and the first efficiency and cycle life of the battery are also reduced.
[0160] Although some specific embodiments of the present application have been described in detail by way of example, it should be understood by those skilled in the art that the above examples are only for illustration, not for limiting the scope of the present application. It should be understood by those skilled in the art that the above embodiments may be modified without departing from the scope and spirit of the present application. The scope of the present application is defined by the appended claims.
Claims
1. A negative electrode sheet, characterized in that: include: Anode current collector; A negative electrode active layer, the negative electrode active layer is disposed on at least one side surface of the negative electrode current collector; The negative electrode active layer comprises silicon dioxide nanowires, and the mass proportion of the silicon dioxide nanowires in the negative electrode active layer is 0.1%-5%.
2. The negative electrode sheet according to claim 1, characterized in that: The mass proportion of the silicon dioxide nanowires in the negative electrode active layer is 0.5%-2.0%.
3. The negative electrode sheet according to claim 1, characterized in that: The negative electrode active layer includes a negative electrode active material and a plurality of the silicon dioxide nanowires. The plurality of the silicon dioxide nanowires are overlapped to form a three-dimensional framework. At least a portion of the negative electrode active material is filled in the three-dimensional framework.
4. The negative electrode sheet according to claim 3, characterized in that: The negative electrode active material accounts for 80% to 98% by mass of the negative electrode active layer.
5. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The dielectric constant of the silicon dioxide nanowires is in the range of 1.5-4.
0.
6. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The negative electrode active layer comprises a first dressing layer and a second dressing layer, wherein the first dressing layer is arranged on at least one side of the surface of the negative electrode current collector, and the second dressing layer is arranged on a side of the first dressing layer away from the negative electrode current collector; The first dressing layer and / or the second dressing layer include silicon dioxide nanowires.
7. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The silicon dioxide nanowire has a pore structure, and the pore diameter of the pore structure ranges from 2nm to 50nm.
8. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The length of the silicon dioxide nanowire is in the range of 0.5 μm to 50 μm; and / or the diameter of the silicon dioxide nanowire is in the range of 5 nm to 100 nm; and / or the specific surface area of the silicon dioxide nanowire is in the range of 50 m 2 / g-1000m 2 / g.
9. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The single surface density of the negative electrode active layer is in the range of 500 g / m 2 -700g / m 2 .
10. The negative electrode sheet according to any one of claims 1 to 4, characterized in that: The negative electrode active layer also includes a conductive agent, a thickener and a binder; the conductive agent accounts for 0-5% of the mass of the negative electrode active layer, the thickener accounts for 0.5%-5% of the mass of the negative electrode active layer, and the binder accounts for 0.5%-5% of the mass of the negative electrode active layer.
11. A battery, characterized in that: The negative electrode sheet comprises the negative electrode sheet as described in any one of claims 1 to 10.
12. An electrical device, characterized in that: Comprising the battery of claim 11.
Citation Information
Cited By
Lithium ion battery, battery assembly and electric device
CN121215846A